Target-site and non-target-site resistance mechanisms confer multiple resistance to glyphosate and 2,4-D in Carduus acanthoides - Palma Bautista, Candelario (2023)
Carduus acanthoides L. is mainly a range-land weed, but in the 2010s has begun to invade GM crop production systems in Córdoba (Argentina), where glyphosate and 2,4-D have been commonly applied. In 2020, C. acanthoides was found with multiple resistance to these two herbicides. In this study, the mechanisms that confer multiple resistance to glyphosate and 2,4-D, were characterized in one resistant (R) population of C. acanthoides in comparison to a susceptible (S) population. No differences in 14C-herbicide absorption and translocation were observed between R and S populations. In addition, 14C-glyphosate was well translocated to the shoots (∼30%) and roots (∼16%) in both R and S plants, while most of 14C-2,4-D remained restricted in the treated leaf. Glyphosate metabolism did not contribute to resistance of the R population; however, as corroborated by malathion pretreatment, the mechanism of resistance to 2,4-D was enhanced metabolism (63% of the herbicide) mediated by cytochrome P450 (Cyt-P450). No differences were found in baseline EPSPS activity, copy number, and/or gene expression between the R and S populations, but a Pro-106-Ser mutation in EPSPS was present in the R population. Multiple resistances in the R population of C. acanthoides from Argentina were governed by target site resistance (a Pro-106 mutation for glyphosate) and non-target site resistance (Cyt-P450-based metabolic resistance for 2,4-D) mechanisms. This is the first case of resistance to glyphosate and 2,4-D confirmed for this weed in the world.